Extent of the External Auditor’s Understanding of the Concept of CSR Study of a sample of auditors in Iraq - Mowaffaq Abdul Hussain Mohammed; Safaa Ibrahim Atteih (Journal of Madenat Alelem University College, 2020)
The development of accounting from the mere keeping of records and the preparation of financial statements that explain the fairness of the financial center to the analysis of this information to reach conclusions not only on the reality and future of the accounting unit but also the interrelationship between those units and the environment and society in which it operates. The goal of the research is to define the concept of auditing. The extent of its application by the external auditor in Iraq and as a result of the broad scope of the auditor’s work in achieving the social responsibility requirements of the economic units. To achieve the objectives of the research, a questionnaire was prepared and distributed to the external auditors The researchers have found that the auditor in Iraq is aware of the social audit, but they do not apply and do not prepare a social responsibility audit program when examining the financial statements of their clients. The researchers recommended that the external auditor develops an action plan and audit program to audit the social responsibility and to disclose the social activities of the unit.